XRF (X-ray fluorescence) applied to characterization of unconventional Woodford Shale (Devonian, U.S.A.) lateral well heterogeneity. (15th October 2019) - Zhang, Jing; Zeng, Yijin; Slatt, Roger
Highlights: Innovative application of XRF on horizontal well cutting measurements. XRF reveals capability to characterize reservoir heterogeneity at small scales. XRF bunch analysis is high in economic and time efficiency compared to well logs. Hydraulic fracturing design can be optimized by XRF interpretation. Abstract: X-ray fluorescence (XRF) was applied to measuring drill cuttings in order to characterize reservoir heterogeneity along a horizontal wellbore that landed in the organic-rich Woodford Shale. The measured XRF data profile which is composed of different paleoenvironmental and sedimentary element proxies were interpreted along with microseismic data distribution patterns from hydraulic fracturing. Three representative microseismic event distribution patterns were selected as demonstrations for reservoir heterogeneity's impact on hydraulic fracturing efficiency, reflected by the corresponding variation in the XRF profile. This case study indicates that heterogeneity is a non-negligible factor in unconventional shale reservoirs and controls the efficiency of hydraulic fracturing. XRF is not restricted to conduct vertical scale chemostratigraphic characterization on core and outcrop, but also applicable for lateral well heterogeneity characterization near wellbore, which helps optimizing hydraulic fracturing design and ultimately reducing the risk of production failure.